Acute effects of dynamic whole body vibration in well trained track & field sprinters - Gerakaki, M.; Evangelidis, P.; Tziortzis, S.; Paradisis, G. P. (Journal of Physical Education and Sport, 2013)
Whole-body vibration is a neuromuscular training method and has been suggested as an acute ergogenic aid mode before practice, training and competition activities of athletes. The aim of this study was to investigate the acute effects of a whole-body vibration session on sprint running kinematics and neuromuscular performance in well trained track & field sprinters. 30 sprint athletes participated in this study (age 21.6 ± 4.1 years, height 1.76 ± 5.0 m, body mass 71.2 ± 6.4 kg). Both experimental (with vibration) and control (without vibration) groups performed a single session of whole-body vibration consisted of two dynamic exercises (half squat / lunge) using a body vibration platform (90 s, 50 .z, 2 mm). Performance tests (60m sprint, counter movement jump, muscle power and sit & reach test) were performed before and after 6 min the whole-body vibration session. Counter movement jump was reduced after whole-body vibration by 3.9%, whereas all the other analyzed parameters remained unchanged. The results of this study do not support the use of whole-body vibration as an acute ergogenic aid during standardized warm-up in well trained track and field sprinters.